A Real-Time Energy Consumption and Monitoring for Domestic Houses by using Internet of Things Approach - Azman, Muhammad Asyraaf; Rahman, Rahisham (Evolution in Electrical and Electronic Engineering, 2022)
Nowadays, mitigating domestic energy demand is a crucial concern for consumers. In the same way that one technology evolves into a more advanced one, it also happened in the electrical energy meter. If at first, one traditional energy meter could evolve into a smart energy meter. This study addresses the smart energy meter could be integrated into a portable device where the same concept of the Internet of Things (IoT) platform as a medium of clouding data is applied for conventional use for customers. The use of a microcontroller that is integrated with a serial Wi-Fi module act as the backbone of the system prototype to operate as a medium to upload data that encompassed of sensing scheme and mathematical approaches to obtain the electricity consumption of one consumer. This paper aims to discover instances where consumers might cut power consumption by monitoring overall energy consumption using the SCT013 current clamp transformer as the sensor component. To achieve this goal, a monitoring device-based on real-time data collection must be developed using the IoT medium of the ThingSpeak platform, where the data may be viewed on a PC, laptop, smartphone, etc. Based on the current results, the electricity usage statistics could be displayed graphically or numerically as well as users could observe the maximum and minimum peak consumption at one time period. With this effort, users can manage and control their overuse of energy by lively monitoring real-time electricity consumption.